2020
DOI: 10.1029/2020jb020094
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical Conductivity of Liebermannite: Implications for Water Transport Into the Earth's Lower Mantle

Abstract: Liebermannite (KAlSi3O8) is a principal mineral phase expected to be thermodynamically stable in deeply subducted continental and oceanic crusts. The crystal structure of liebermannite exhibits tunnels that are formed between the assemblies of double chains of edge‐sharing (Si, Al) O6 octahedral units, which act as a repository for large incompatible alkali ions. In this study, we investigate the electrical conductivity of liebermannite at 12, 15, and 24 GPa and temperature of 1500 K to track subduction pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…The A sites are connected to each other to form channels along [001] direction that is likely to further facilitate the mobility of the Na + ions. Similar high electrical conductivity has been observed in liebermannite which also has tunnels that promote the migration of alkali cations (He et al, 2016;Manthilake et al, 2020). Also, fast ionic conduction in solid state has been observed in albite, where Na + ions undergo faster diffusion via the alkali ion cavities in the albite aluminosilicate framework (Hu et al, 2011).…”
mentioning
confidence: 64%
“…The A sites are connected to each other to form channels along [001] direction that is likely to further facilitate the mobility of the Na + ions. Similar high electrical conductivity has been observed in liebermannite which also has tunnels that promote the migration of alkali cations (He et al, 2016;Manthilake et al, 2020). Also, fast ionic conduction in solid state has been observed in albite, where Na + ions undergo faster diffusion via the alkali ion cavities in the albite aluminosilicate framework (Hu et al, 2011).…”
mentioning
confidence: 64%
“…The conductivity ( ) is expressed in S/m, temperature ( ) is in absolute temperature, is the pre-exponential factor in S/m, and is the gas constant in J K −1 mol −1 . We obtain the activation enthalpy and the pre-exponential factor following the combined electrical conductivity 43 , 44 . The notations , indicates distinct conduction mechanisms operating at different temperature intervals 45 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In comprehensive comparisons with previously acquired electrical conductivity results on the hot-pressed sintering polycrystalline quartz reported by Bagdassarov and Delépine (2004) [113], synthetic polycrystalline anorthite reported by [60], as well as the pure aqueous fluid of sodium chloride with the 5% of weight percentage reported by Sinmyo and Keppler (2017) [114], one new origin for the explanation of high conductivity anomaly at the depth ranges from 70 to 120 km was put forward on the base of the released water-bearing fluid during the process of epidote dehydration at high temperature and high pressure. Furthermore, some recently reported electrical conductivity and elastic wave velocity results on hydrous halogen-bearing amphibole, glaucophane, Liebermannite, chlorite, and lawsonite from Manthilake et al [98][99][100][101][102] also confirmed that the dehydration of hydrous minerals will release a large amount of the water-bearing fluids, which can be used to reasonably explain the anomalously seismic and electrical transport behaviors in the region of hot subduction of deep mantle wedges.…”
Section: Electrical Conductivity Of Hydrous Epidotementioning
confidence: 88%
“…It is well known that the electrochemical AC impedance spectroscopy method is one of most efficient technique to measure the electrical conductivity of hydrous minerals and rocks at conditions of high temperatures and high pressures [98][99][100][101][102][103][104][105][106]. Before we launched a complex impedance spectroscopy measurement, the AC signal voltage ranges from 10 mV to 3 V and the scanning frequency ranges from 10 −5 Hz to 3.2 × 10 7 Hz need to be predesignated by virtue of Z-Plot program in the complex impedance spectroscopy analyzer.…”
Section: Experimental Theory and Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation